2016
DOI: 10.1002/stem.2433
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mobilization of Exogenous Mesenchymal Stem Cells to Bone for Fracture Healing and Sex Difference

Abstract: Mesenchymal stem cell (MSC) transplantation has been tested in animal and clinical fracture studies. We have developed a bone-seeking compound, LLP2A-Alendronate (LLP2A-Ale) that augments MSC homing to bone. The purpose of this study was to determine whether treatment with LLP2A-Ale or a combination of LLP2A-Ale and MSCs would accelerate bone healing in a mouse closed fracture model and if the effects are sex dependent. A right mid-femur fracture was induced in two-month-old osterix-mCherry (Osx-mCherry) male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 93 publications
(110 reference statements)
6
61
0
Order By: Relevance
“…However, it is difficult to precisely distinguish the contribution of various sources of progenitors during fracture healing. Our transgenic lineage tracking attempt in combination with microCT scans and histology showed that the fracture callus was initially formed from the periosteum, which was consistent with other reports . ADSC bFGF treatment showed a similar degree of bone formation from the periosteal surface.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is difficult to precisely distinguish the contribution of various sources of progenitors during fracture healing. Our transgenic lineage tracking attempt in combination with microCT scans and histology showed that the fracture callus was initially formed from the periosteum, which was consistent with other reports . ADSC bFGF treatment showed a similar degree of bone formation from the periosteal surface.…”
Section: Discussionsupporting
confidence: 90%
“…The cells were maintained in Mesencult mouse MSC proliferation medium (Stem Cell Technologies Inc., Vancouver, BC, Canada, https://www.stemcell.com/) and used at passage 2. These cells were 99.99% CD45 negative and positive for CD105 (>70%), CD29 (>99%) and Sca1 (>98%) .…”
Section: Methodsmentioning
confidence: 99%
“…Even worse, about 8.9 million suffer from fractures worldwide (Johnell & Kanis, 2006). Activation and migration of mesenchymal stem cells (MSCs) have been shown to play an important role in fracture healing (Yao et al, 2016) and are also decreased with age (Sui, Hu, Zheng, & Jin, 2016). The older the patient, the lower activity of the osteoblast.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been proven to have strong immunosuppressive properties with the ability for self-renewal and self-differentiation (Yao et al, 2016). The presence of MSCs has been shown to promote angiogenesis, increase tissue repair and reduce inflammation, which is important in wound healing (Hadjiargyrou & O'Keefe, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Generally it is divided into inflammatory response period, repair period and plastic period. The three stages are intertwined with each other [3]. Fracture healing requires the processes of hematoma formation, fibrous callus formation, bone callus formation and callus remodeling.…”
Section: Introductionmentioning
confidence: 99%